PROTEOLYTIC CONTAMINANTS OF CRYSTALLINE RIBONUCLEASE - McDonald, Margaret R. (The Rockefeller University Press, 1948)
1. The ability of crystalline ribonuclease to hydrolyze proteins is due to impurities present in the preparations and not to an intrinsic property of the ribonuclease molecule. The amounts of these impurities vary enormously with different preparations. 2. The dangers inherent in the use of crystalline enzymes as specific tools, without assaying them for all possible interfering impurities, are emphasized.